2013
DOI: 10.1109/lpt.2013.2252888
|View full text |Cite
|
Sign up to set email alerts
|

100-Gb/s Wavelength Division Demultiplexing Using a Photonic Crystal Four-Channel Drop Filter

Abstract: We report on the first demonstration of the wavelength demultiplexing of a 100-Gb/s nonreturn to zero signal to four channels at 25 Gb/s, based on resonant structures implemented in GaInP photonic crystals. The device is composed of four filters based on H0 cavities with one common input bus and four drop outputs showing a very small footprint. The measured device characteristics show good performances in terms of transmission and crosstalk with insertion losses of 11 dB on the best port. System measurements h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In the process of migrating to a higher port count WSS without introducing a complex configuration or loss increase entails the use of planar lightwave circuits (PLCs) [261]. The design and fabrication of siliconbased integrated multichannel filter cascaded by a wavelength de-multiplexer has been reported by numerous groups [262], [263], [264]. The multichannel filtering is achieved by a DI structure and the de-multiplexing is performed by an AWG.…”
Section: B Passive Optical Filtersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of migrating to a higher port count WSS without introducing a complex configuration or loss increase entails the use of planar lightwave circuits (PLCs) [261]. The design and fabrication of siliconbased integrated multichannel filter cascaded by a wavelength de-multiplexer has been reported by numerous groups [262], [263], [264]. The multichannel filtering is achieved by a DI structure and the de-multiplexing is performed by an AWG.…”
Section: B Passive Optical Filtersmentioning
confidence: 99%
“…The multichannel filtering is achieved by a DI structure and the de-multiplexing is performed by an AWG. Many other methods can also perform the desired functions, such as the dielectric multilayered filters [262], the photonic crystal based drop filter [263], and the plasmonic nanodisk cavities [264]. One of the main issues with this technique is that the channel count in the demonstrations to date are pretty low.…”
Section: B Passive Optical Filtersmentioning
confidence: 99%
“…Fig. 3 shows in details the experimental setup employed for the BER measurements in the WDM configuration [11]. It must be pointed out that the setup for the single channel measurement is the same, except that in this case only the source pertinent to the examined path (channel under test) is active.…”
Section: Ber Evaluation Setupmentioning
confidence: 99%
“…To realize smaller WDM demultiplexers, those based on Si PC are being developed. [17][18][19][20][21][22][23][24] For example, Song et al 18 demonstrated two-dimensional (2-D) PC cavities-based 16-channel WDM demultiplexer with 628-GHz channel spacing, and the footprint of per channel is 12 μm 2 . Takahashi et al 21 demonstrated 2-D PC cavities-based 32-channel out-of-plane WDM demultiplexer with 100-GHz channel spacing, and the footprint of per channel is ∼130 μm 2 .…”
Section: Introductionmentioning
confidence: 99%